Optimasi Pengendalian Bahan Baku Phospat Menggunakan Metode Economic Order Quantity (EOQ) dan Periodic Order Quantity (POQ) di PT XYZ - Suparno Suparno; Nailul Izzah; Anik Rufaidah; Narto Narto (Universitas Teuku Umar, 2026)
This study addresses the importance of raw material inventory control in maintaining production continuity and minimizing operational costs in manufacturing companies. Ineffective inventory policies may lead to overstock or stockout conditions, both of which negatively impact efficiency and cost performance. Therefore, this research aims to determine the most optimal inventory control method for phosphate raw materials at PT. XYZ by comparing the Economic Order Quantity (EOQ) and Periodic Order Quantity (POQ) methods. A quantitative approach was employed using demand forecasting data, ordering cost, holding cost, and lead time. The annual demand for phosphate raw materials was estimated at 3,875,850 kg. The results show that the company’s current policy generates a total inventory cost of Rp26,629,000 per year. The EOQ method produces an optimal order quantity of 3,742.56 kg per order with a total inventory cost of Rp42,750,797 per year. Meanwhile, the POQ method results in an optimal ordering interval of every four months, with an order quantity of 1,291,950 kg and a significantly lower total inventory cost of Rp9,385,000 per year. Both methods yield the same reorder point (ROP) of 42,476 kg. Based on the analysis, the POQ method is the most efficient inventory control approach due to its ability to minimize total inventory costs and better accommodate fluctuating demand patterns. However, its implementation should consider warehouse capacity and operational constraints.